Translating Jonah’s narration and poetry into Sabaot : towards a participatory approach to Bible translation (PABT) - Chemorion, Diphus Chosefu (Stellenbosch : Stellenbosch University, 2008)
Thesis (DTh (Old and New Testament))--Stellenbosch University, 2008.